Manganese-enhanced magnetic resonance imaging of the spinal cord in rats with formalin-induced pain. (December 2019) - Cha, Myeounghoon; Lee, Kyuhong; Won, Jun Sik; Lee, Bae Hwan
Highlights: Mn 2+ enhancement is related to signal transduction in the spinal cord. Mn 2+ preferably accumulates in excited neuronal cells/axons, and inactivated neurons show less contrast enhancement. MEMRI is an adequate tool for monitoring signal transduction in the spinal cord. Abstract: Manganese-enhanced magnetic resonance imaging (MEMRI) is based on neuronal activity-dependent manganese uptake, and provides information about nervous system function. However, systematic studies of pain processing using MEMRI are rare, and few investigations of pain using MEMRI have been performed in the spinal cord. Herein, we investigated the pain dependence of manganese ions administered in the rat spinal cord. MnCl2 was administered into the spinal cord via an intrathecal catheter before formalin injection into the right hind paw (50 μL of 5% formalin). The duration of flinching behavior was recorded and analyzed to measure formalin-induced pain. After the behavioral test, rats were sacrificed with an overdose of urethane (50 mg/kg), and spine samples were extracted and post-fixed in 4% paraformaldehyde solution. The samples were stored in 30% sucrose until molecular resonance (MR) scanning was performed. In axial Mn 2+ enhancement images of the spinal cord, Mn 2+ levels were found to be significantly elevated on the ipsilateral side of the spinal cord in formalin-injected rats. To confirm pain-dependent Mn enhancement in the spinal cord, c-Fos expression was analyzed, and was found to be increased in the formalin-injected rats. These results indicate that MEMRI is useful for functional analysis of the spinal cord under pain conditions. The gray matter appears to be the focus of intense paramagnetic signals. MEMRI may provide an effective technique for visualizing activity-dependent patterns in the spinal cord.